Spirituality as a subject of philosophical comprehension in the creative heritage of S.B. Krymsky - Мокляк, Л. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
In the article the concept of spirituality in the creative heritage of the outstanding Ukrainian philosopher S.B. Krymsky is carried out.